2020
DOI: 10.1097/01.ogx.0000695068.77197.3a
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Salpingectomy for Prevention of Ovarian Cancer at the Time of Elective Laparoscopic Cholecystectomy

Abstract: (Abstracted from BJS 2020;107:519–524) The majority of ovarian cancers are now believed to originate in the fimbriae of the fallopian tubes as serous tubal intraepithelial carcinomas (STICs). Removal of the fallopian tubes (salpingectomy) has been associated with a reduced risk of developing ovarian cancer, leading to gynecologic societies recommending prophylactic salpingectomy at the time of pelvic surgery in appropriate women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Additionally, it remains unclear (with likely variation across provinces) if general surgeons providing this service would receive any renumeration. In the study by Tomasch et al (2020), renumeration was not available and was reported as a barrier to completing these procedures [63].…”
Section: Consentmentioning
confidence: 99%
“…Additionally, it remains unclear (with likely variation across provinces) if general surgeons providing this service would receive any renumeration. In the study by Tomasch et al (2020), renumeration was not available and was reported as a barrier to completing these procedures [63].…”
Section: Consentmentioning
confidence: 99%